Interindividual variation in DNA methylation at a putative POMC metastable epiallele is associated with obesity - Kühnen, P.; Handke, D.; Waterland, R.A.; Hennig, B.J.; Silver, M.; Fulford, A.J.; Domínguez Salas, Paula; Moore, S.E.; Prentice, A.M.; Spranger, J.; Hinney, A.; Hebebrand, J.; et al. (Elsevier, 2016)
The estimated heritability of human BMI is close to 75%, but identified genetic variants explain only a small fraction of interindividual body-weight variation. Inherited epigenetic variants identified in mouse models named "metastable epialleles" could in principle explain this "missing heritability." We provide evidence that methylation in a variably methylated region (VMR) in the pro-opiomelanocortin gene (POMC), particularly in postmortem human laser-microdissected melanocyte-stimulating hormone (MSH)-positive neurons, is strongly associated with individual BMI. Using cohorts from different ethnic backgrounds, including a Gambian cohort, we found evidence suggesting that methylation of the POMC VMR is established in the early embryo and that offspring methylation correlates with the paternal somatic methylation pattern. Furthermore, it is associated with levels of maternal one-carbon metabolites at conception and stable during postnatal life. Together, these data suggest that the POMC VMR may be a human metastable epiallele that influences body-weight regulation.